2012
DOI: 10.1097/aog.0b013e3182393f86
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise During Pregnancy to Prevent Gestational Diabetes

Abstract: : ClinicalTrials.gov, www.clinicaltrials.gov, NCT00476567.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
249
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(259 citation statements)
references
References 25 publications
5
249
0
5
Order By: Relevance
“…In a study of healthy pregnant women, mild physical activity was found to lower the risk of developing gestational diabetes (26). In contrast, a recent randomized control trial in women of normal body weight showed that exercise during pregnancy did not decrease the prevalence of gestational diabetes compared with sedentary controls (43). Few human studies have investigated offspring effects of maternal exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of healthy pregnant women, mild physical activity was found to lower the risk of developing gestational diabetes (26). In contrast, a recent randomized control trial in women of normal body weight showed that exercise during pregnancy did not decrease the prevalence of gestational diabetes compared with sedentary controls (43). Few human studies have investigated offspring effects of maternal exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Seven randomized controlled trials, published between 2009 and 2012, are summarized in Table 1 [32][33][34][35][36][37][38]. In contrast to observational data, a recent summary of five of these studies concluded that they could find no clear effect on preventing GDM [39].…”
Section: Can Exercise Prevent Gdm?mentioning
confidence: 99%
“…Therefore, it is likely that a lack of statistical power and the failure to control for significant confounding factors, such as diet and gestational weight gain, may have contributed to nonsignificant findings in both individual trials and the published meta-analysis. Power calculations to determine adequate sample size were reported in only one of the five included studies [34]. In this study, the authors estimated that 381 patients were required in each group.…”
Section: Can Exercise Prevent Gdm?mentioning
confidence: 99%
See 2 more Smart Citations